Perancangan Company Profile Berbasis Motion Graphic Sebagai Media Publikasi Pada Tonec Vision Jombor Kecamatan Tuntang - Arie Atwa Magriyanti; Danang Danang; Mukhammad Ibnu Khalim (Jurnal Elektronika dan Teknik Informatika Terapan ( JENTIK ), 2023)
Tonec Vision is a company engaged in multimedia, photography, and graphic design. The address is Griya harmony No. 02 Jombor Village, Tuntang District. This company offers quite a variety of services including video shooting, pre-wedding photos, weddings, then digital printing. In today's digital era, which is advancing rapidly, it is easier for humans to receive information. This has a big influence on business people, to do a lot of innovation. Publication media such as company profiles are needed by business people. Company profile aims to inform the existence of a company with detailed information. Information that must be in a company includes company history, vision and mission, form of service or product and company contacts. In addition, the company profile itself has an important role in the business growth of a company. So far, the Tonec Vision company in publishing its business is still through print media such as brochures, mmt, and through the website. This is still lacking in providing information to the public, so it is necessary to add interesting media to attract people to the company. The purpose of this study is to design a motion graphic-based company profile, this company profile design is used to complement the previous publication media. The final result of this company profile is in the form of interactive media which contains company information made with motion graphic techniques. In the use of motion graphics, different elements such as animation, photography, typography, and music are combined into an attractive video. The results of the validation values obtained from media experts are 38, material experts are 39, and product users are 38.33 which are classified in the Very good category, so this company profile is declared valid to be used.